Hubungan Antara Metode Pengajaran Dosen dan Perkembangan Kompetensi Mahasiswa - Harefa, Rifadil Anugrah; Harefa, Tiara Chandra Sari (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This research aims to identify the relationship between lecturers' teaching methods and the development of student competencies in higher education. Student competencies include critical thinking skills, communication skills, problem solving abilities, and other practical skills needed in the professional world. This article uses a literature review approach that analyzes several relevant studies on the influence of various teaching methods, such as lectures, group discussions, problem-based learning (PBL), and project-based learning (PJBL), on the development of student competencies. Based on existing studies, it was found that interactive learning methods based on student participation, such as PBL and PJBL, have a more significant impact on student competence compared to conventional lecture methods. These results provide important insights for the development of higher education curricula to improve the quality of student competencies.